Solidarność Portowców . biuletyn informacyjny, no. 206, 1981 - Komisja Zakładowa NSZZ "Solidarność" Zarządu Portu Gdynia, [ed. committee "BI"] (NSZZ "Solidarność" ZP Gdynia, 1981)
Print run: 4500-6000 copies